2016
DOI: 10.5539/sar.v5n4p94
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Farm Income Stabilization Insurance Program on Production Decisions in the Quebec Pork Industry: An Empirical and Theoretical Analysis

Abstract: The Farm Income Stabilization Insurance Program (ASRA) is an agricultural program implemented in several agricultural sectors in Quebec, including the pork sector. This article aims to empirically assess the effects of this program on production decisions in the pork industry in Quebec using a Vector Error Correction Model (VEC). As variables we used the pig supply, the price of pork, and stabilized income. The dataset contains information about the pork sector which cover the period 1981-2014. The annual aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In Asia and sub-Saharan Africa, incomes of smallholder farmers are low and characterized by sharp fluctuations ( Fanzo, 2017 ). This income instability is due to several factors that influence the supply of agricultural produce, such as weather changes and biological crises like disease outbreaks and pest invasions ( Atozou and Lawin, 2016 ). With agricultural production taking considerable time to complete, the cyclical shortage in supply leads to uncertainty in returns ( Gilbert and Morgan, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Asia and sub-Saharan Africa, incomes of smallholder farmers are low and characterized by sharp fluctuations ( Fanzo, 2017 ). This income instability is due to several factors that influence the supply of agricultural produce, such as weather changes and biological crises like disease outbreaks and pest invasions ( Atozou and Lawin, 2016 ). With agricultural production taking considerable time to complete, the cyclical shortage in supply leads to uncertainty in returns ( Gilbert and Morgan, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the variable "commodity price" was statistically significant (<0.01) and positively related to net-income of fish farmers. The price of a commodity has been shown to affect the income of farmers either positively or negatively (Demeke & Balie, 2016) depending on the demand, quantity supplied and several other factors such as weather changes and biological crisis (Atozou & Lawin, 2016). This means that under favourable conditions, an increase in the price of a commodity will positively result to an increase in income.…”
Section: Socio-economic Determinants Of Net-farm Incomementioning
confidence: 99%
“…In Quebec, the pork sector is covered by the Agricultural Income Stabilization Insurance Program. Atozou and Lawin (2016) showed that this program leads to a disconnection between production decisions and market conditions, thus generating overproduction regardless of the market price.…”
Section: Agricultural Policy and Market Structure In Pork Sectormentioning
confidence: 99%